Comparing the importance of freshwater flows driving primary production in three tropical estuaries. (August 2021) - Burford, Michele A.; Faggotter, Stephen J.
Abstract: Estuaries in the tropical Gulf of Carpentaria (GOC) in Australia are under increasing pressure from catchment water development, potentially affecting productivity. We examined the potential effect of changes in freshwater inputs on the primary productivity of three estuaries (Flinders, Gilbert and Mitchell Rivers). The addition of nutrients stimulated mudflat primary production in all estuaries at multiple sampling times, suggesting chronic nutrient limitation. All three estuaries were productive with the Flinders estuary being the most productive of the three estuaries, compared to the Gilbert and Mitchell estuaries. This is despite the fact that the Flinders estuary has the shortest period of freshwater flow and more variable flows from year-to-year compared with the other estuaries. This makes the Flinders highly vulnerable to excessive water development. This study suggests that water extraction which significantly reduces freshwater inputs and associated nutrients has the potential to impact on productivity within these estuaries.